Effects Of Light On The Distributions, Photosynthesis And Recovery Of Halophila ovalis (R. Br.) Hook. f. In Pulau Korea (Pulau Gazumbo), Penang - Jonik, Michelle Glory G (2020)
From the 72 global species diversity of seagrass, there are 16 species from different genera were recorded throughout the 78 sites in Malaysia. To date, there are six seagrass habitats reported in the northern region of Peninsular Malaysia and one of it is this study site, Pulau Korea, Penang. The study site is rich in biodiversity with a significant number of coastal communities relying on it for their livelihood. However, Penang Island is a highly urbanised city state in Northern region of Malaysia and Penang States Development Corporation had proposed to reclaim Pulau Korea. Despite all the coastal developments adjacent to the study site which will disrupt the water quality, there have been limited studies of seagrass conditions in terms of photo-physiology nor the recent distribution are since year 2016. Thus, this study was to provide an updated report on the distribution, biomass and photo-physiology of Halophila ovalis in the intertidal zone of Pulau Korea. The distribution was estimated based on seagrass percentage cover, while the health of seagrass was monitored through the photo-physiological performance by using chlorophyll fluorescence technique. The findings indicated that the total estimated area of seagrass area in Pulau Korea was approximately 4.49 acres (39.8 ± 2.03%) and was classified as moderate coverage with Braun-Blanquet scale score 3. However, seagrass population in Pulau Korea was low, with only 3 identified seagrass species (H. ovalis as the dominant seagrass, H. beccarii and Enhalus acoroides) as compared with other seagrass bed in Merambong, Johor that have more seagrass species.